2013
DOI: 10.1038/onc.2013.523
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of the microRNA cluster at the Dlk1-Dio3 locus in lung adenocarcinoma

Abstract: Mice in which lung epithelial cells can be induced to express an oncogenic KrasG12D develop lung adenocarcinomas in a manner analogous to humans. A myriad of genetic changes accompany lung adenocarcinomas, many of which are poorly understood. To get a comprehensive understanding of both the transcriptional and post-transcriptional changes that accompany lung adenocarcinomas, we took an omics approach in profiling both the coding genes and the non-coding small RNAs in an induced mouse model of lung adenocarcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 64 publications
1
53
0
Order By: Relevance
“…Indeed, they were overexpressed in the lungs of mice at the late embryonic stage or newborn mice and then decrease dramatically during the first weeks of life (45,46). A recent study that performed RNAseq in KRAS G12D transgenic tumors found that miRNAs encoded at the Dlk1-Dio3 locus on mouse chromosome 12qF1 were consistently increased in tumors as compared with nonmalignant lung (47). Interestingly, these miRNAs were repressed when KRAS G12D cells were grown in vitro and were reactivated when transplanted in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, they were overexpressed in the lungs of mice at the late embryonic stage or newborn mice and then decrease dramatically during the first weeks of life (45,46). A recent study that performed RNAseq in KRAS G12D transgenic tumors found that miRNAs encoded at the Dlk1-Dio3 locus on mouse chromosome 12qF1 were consistently increased in tumors as compared with nonmalignant lung (47). Interestingly, these miRNAs were repressed when KRAS G12D cells were grown in vitro and were reactivated when transplanted in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…During mouse embryogenesis, the microRNA (miRNA) members of the DLK1-DIO3 cluster have been shown to be elevated in the developing central nervous system, skeletal muscle, liver and lung (3). Similarly, several transgenic mouse models of prostate, liver and lung cancer also exhibit elevated levels of DLK1-DIO3 cluster miRNA members (48). The functions of many of these miRNAs within this imprinted region remain largely unexplored in cancer biology, specifically for EMT and cancer stemness.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, Greeve et al (8) have suggested that most types of carcinoma, including hepatocellular carcinoma, are not associated with aberrant editing of the mRNAs encoding APOB, novel APOBEC1 target 1, or neurofibromin 1. However, more recently, APOBEC1-driven mRNA editing has been shown to be associated with lung adenocarcinoma (9); therefore, the role of aberrant APOBEC1-driven mRNA editing in tumorigenesis requires further clarification.…”
Section: Apolipoprotein B (Apob)mentioning
confidence: 99%
“…Ectopic expression of APOBEC1 occurs in hepatocellular carcinoma (8), lung carcinoma (9), carcinoma in situ cells of the adult testis (10), and contused rat spinal cords (11). A consensus p53 response element in the APOBEC1 promoter can drive expression of the gene in non-intestinal cell types.…”
Section: Apolipoprotein B (Apob)mentioning
confidence: 99%